Is the small heat shock protein αB-crystallin an oncogene? - Saal, Sofia K. Gruvberger; Parsons, Ramon (The Journal of Clinical Investigation, 2006)
In the last 5 years, global gene expression profiling has allowed for the subclassification of the heterogeneous disease of breast cancer into new subgroups with prognostic significance. However, for most subgroups, the nature of the contributions of individual genes to the clinical phenotypes remains largely unknown. In this issue of the JCI, Moyano and colleagues further examine the oncogenic potential of the small heat shock protein α-basic–crystallin, commonly expressed in tumors of the basal-like breast cancer subtype associated with poor prognosis, and show that it is an oncogenic protein in the breast.